qanda-logo
search-icon
Symbol
apple-logo
google-play-logo

Calculator search results

Formula
Solve the system of equations
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
Graph
$4 y + 3 x = 8$
$8 x - 9 y = - 77$
$x$Intercept
$\left ( \dfrac { 8 } { 3 } , 0 \right )$
$y$Intercept
$\left ( 0 , 2 \right )$
$x$Intercept
$\left ( - \dfrac { 77 } { 8 } , 0 \right )$
$y$Intercept
$\left ( 0 , \dfrac { 77 } { 9 } \right )$
$\begin{cases} 4y+3x = 8 \\8x-9y = -77 \end{cases}$
$x = - 4 , y = 5$
Solve the system of equations
$\begin{cases} 4 y + 3 x = 8 \\ 8 x - 9 y = - 77 \end{cases}$
$ $ Solve a solution to $ x$
$\begin{cases} \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 4 } { 3 } } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 8 } { 3 } } \\ 8 x - 9 y = - 77 \end{cases}$
$\begin{cases} \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 4 } { 3 } } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 8 } { 3 } } \\ \color{#FF6800}{ 8 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 9 } \color{#FF6800}{ y } = \color{#FF6800}{ - } \color{#FF6800}{ 77 } \end{cases}$
$ $ Substitute the given $ x $ value into the equation $ 8 x - 9 y = - 77$
$\color{#FF6800}{ 8 } \left ( \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 4 } { 3 } } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 8 } { 3 } } \right ) \color{#FF6800}{ - } \color{#FF6800}{ 9 } \color{#FF6800}{ y } = \color{#FF6800}{ - } \color{#FF6800}{ 77 }$
$\color{#FF6800}{ 8 } \left ( \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 4 } { 3 } } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 8 } { 3 } } \right ) \color{#FF6800}{ - } \color{#FF6800}{ 9 } \color{#FF6800}{ y } = \color{#FF6800}{ - } \color{#FF6800}{ 77 }$
$ $ Solve a solution to $ y$
$\color{#FF6800}{ y } = \color{#FF6800}{ 5 }$
$\color{#FF6800}{ y } = \color{#FF6800}{ 5 }$
$ $ Substitute the given $ y $ value into the equation $ x = - \dfrac { 4 } { 3 } y + \dfrac { 8 } { 3 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 4 } { 3 } } \color{#FF6800}{ \times } \color{#FF6800}{ 5 } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 8 } { 3 } }$
$x = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 4 } { 3 } } \color{#FF6800}{ \times } \color{#FF6800}{ 5 } + \dfrac { 8 } { 3 }$
$ $ Calculate the product of rational numbers $ $
$x = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 20 } { 3 } } + \dfrac { 8 } { 3 }$
$x = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 20 } { 3 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 8 } { 3 } }$
$ $ Find the sum or difference of the fractions $ $
$x = \color{#FF6800}{ - } \color{#FF6800}{ 4 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 4 }$
$ $ The possible solutions are as follows $ $
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 4 } , \color{#FF6800}{ y } = \color{#FF6800}{ 5 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 4 } , \color{#FF6800}{ y } = \color{#FF6800}{ 5 }$
$ $ Check if it is the solution to the system of equations $ $
$\begin{cases} \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 5 } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 4 } \right ) = \color{#FF6800}{ 8 } \\ \color{#FF6800}{ 8 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 4 } \right ) \color{#FF6800}{ - } \color{#FF6800}{ 9 } \color{#FF6800}{ \times } \color{#FF6800}{ 5 } = \color{#FF6800}{ - } \color{#FF6800}{ 77 } \end{cases}$
$\begin{cases} \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 5 } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 4 } \right ) = \color{#FF6800}{ 8 } \\ \color{#FF6800}{ 8 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 4 } \right ) \color{#FF6800}{ - } \color{#FF6800}{ 9 } \color{#FF6800}{ \times } \color{#FF6800}{ 5 } = \color{#FF6800}{ - } \color{#FF6800}{ 77 } \end{cases}$
$ $ Simplify the equality $ $
$\begin{cases} \color{#FF6800}{ 8 } = \color{#FF6800}{ 8 } \\ \color{#FF6800}{ - } \color{#FF6800}{ 77 } = \color{#FF6800}{ - } \color{#FF6800}{ 77 } \end{cases}$
$\begin{cases} \color{#FF6800}{ 8 } = \color{#FF6800}{ 8 } \\ \color{#FF6800}{ - } \color{#FF6800}{ 77 } = \color{#FF6800}{ - } \color{#FF6800}{ 77 } \end{cases}$
$ $ Since it is true in both equations, it is the solution of the system of equations $ $
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 4 } , \color{#FF6800}{ y } = \color{#FF6800}{ 5 }$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture
apple-logo
google-play-logo